GOALS AND TASKS OF DEVELOPMENT OF LOCAL STATE AUTHORITIES IN UZBEKISTAN - Isomiddinov Eldor Botirovich (Web of Journals Publishing, 2025)
The article discusses the modernization process of local self-government in Uzbekistan during independence. At the same time, the author provides information on several proposals to attract innovations to the industry and talks about plans to reform local authorities.
Keywords: Public administration, executive power system, local government, modernization, innovation, optimization, control system, liberalize.